ChemInform Abstract: Oligomeric Rare‐Earth Metal Cluster Complexes with Endohedral Transition Metal Atoms. Issue 44 (4th November 2014) - Steinberg, Simon; Zimmermann, Sina; Bruehmann, Matthias; Meyer, Eva; Rustige, Christian; Wolberg, Marike; Daub, Kathrin; Bell, Thomas; Meyer, Gerd
Abstract Comproportionation reactions of LnX3 (Ln: Sc, Y, La, Gd, Tb, Dy, Ho and X: Cl, Br, I) with the respective rare‐earth metals Ln and transition metals M (M: Ru, Rh, Os, Ir, Fe, Co) at 800—1050 °C leads to the formation of 19 new compounds.